Fish Species and Morphological Characters in Parit Nanas Peat Waters, Pontianak City, West Kalimantan - Fadilla, Tri Ainun; Saputra, Firman; Rima Setyawati, Tri (LenteraBio : Berkala Ilmiah Biologi, 2025)
Peatland aquatic ecosystems are unique and provide critical habitats for various freshwater fish species. However, they are highly susceptible to degradation caused by land clearing, drought, fires, and pollution. These disturbances pose significant threats to the survival of native fish species, many of which remain taxonomically unresolved or insufficiently studied. This study aimed to identify fish species and describe their morphological characteristics, as well as evaluate the environmental parameters of peatland waters in Parit Nanas, North Pontianak District, Pontianak City. Sampling was conducted purposively from October to December 2021 at five stations, with four replications per station. A total of 34 fish species from 26 genera and 14 families were recorded, with Osphronemidae, Siluridae, Cyprinidae, and Danionidae being the most frequently encountered families. Each species exhibited distinct morphological traits, analyzed through qualitative descriptive methods. The environmental parameters measured, including temperature, pH, depth, turbidity, current velocity, dissolved oxygen (DO), and total dissolved solids (TDS), indicated that the waters of Parit Nanas still support fish survival. These results suggest that Parit Nanas peatlands sustain a diverse assemblage of freshwater fish, particularly those adapted to acidic and low-oxygen conditions.